2019
DOI: 10.1002/gj.3515
|View full text |Cite
|
Sign up to set email alerts
|

Anatectic origin and geological significance of the Neoarchean ~2.5 Ga charnockite in the Jining area, northern North China Craton

Abstract: The Neoarchean charnockite of Yinshan Block has been a hot topic into understanding the Precambrian geology of the North China Craton. Although there is a broad consensus that the charnockite is usually related to granulite‐facies metamorphism, its petrogenesis and tectonics still remain controversial. We present a comparative study of the petrography, geochemistry, and geochronology of charnockite and intermediate–basic granulite in the Jining area along the northern margin of the North China Craton. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 111 publications
2
15
0
Order By: Relevance
“…Geochemical characteristics indicate that low-Sr charnockite may be related to later metamorphism, whereas high-Sr charnockite were most likely not affected by late metamorphism. The results of geochronology show that the charnockites in the early Precambrian basement are widely affected by the post-metamorphism, and The study results of the geochronology show that the charnockites in the early Precambrian basement are widely affected by the post-metamorphism, and it is related to the regional metamorphism of the northern margin of the NCC at ~2.45 Ga , ~1.95 and ~1.85 (Li et al, 2000;Zhao et al, 2005;Dong et al, 2007;Jian et al, 2008;Wan et al, 2008;Li et al, 2011;Jian et al, 2012;Ma et al, 2013a;Ma et al, 2013b;Ma et al, 2013c;Guo et al, 2012;Liu et al, 2013;Cai et al, 2014;Bai et al, 2015;Xu et al, 2015;Ma et al, 2016;Yang et al, 2016;Shi et al, 2018). Therefore, we selected high Sr samples for corresponding study.…”
Section: Effect Of Metamorphic Superimposedmentioning
confidence: 93%
See 4 more Smart Citations
“…Geochemical characteristics indicate that low-Sr charnockite may be related to later metamorphism, whereas high-Sr charnockite were most likely not affected by late metamorphism. The results of geochronology show that the charnockites in the early Precambrian basement are widely affected by the post-metamorphism, and The study results of the geochronology show that the charnockites in the early Precambrian basement are widely affected by the post-metamorphism, and it is related to the regional metamorphism of the northern margin of the NCC at ~2.45 Ga , ~1.95 and ~1.85 (Li et al, 2000;Zhao et al, 2005;Dong et al, 2007;Jian et al, 2008;Wan et al, 2008;Li et al, 2011;Jian et al, 2012;Ma et al, 2013a;Ma et al, 2013b;Ma et al, 2013c;Guo et al, 2012;Liu et al, 2013;Cai et al, 2014;Bai et al, 2015;Xu et al, 2015;Ma et al, 2016;Yang et al, 2016;Shi et al, 2018). Therefore, we selected high Sr samples for corresponding study.…”
Section: Effect Of Metamorphic Superimposedmentioning
confidence: 93%
“…There are also some Neoarchean-Paleoproterozoic high-grade metamorphic complex rocks widely distributed in the khondalite series Belt and Yinshan Block, more and more studies have shown the metamorphic ages of ~2.5 Ga and ~1.95 Ga are widespread of the NCC (Jian et al,2005(Jian et al, , 2012Ma et al, 2013aMa et al, . 2013bWang et al, 2015;Guo et al, 2001;Wang et al, 2005;Wan et al, 2006Wan et al, , 2009Wan et al, , 2011Wan et al, , 2013aWan et al, , 2013bWan et al, , 2015Santosh et al, 2006Santosh et al, , 2007aSantosh et al, , 2007bXu et al, 2011;Dong et al, 2013;Cai et al, 2014;Ma et al, 2015;Chen et al, 2017;Shi et al, 2018Shi et al, , 2019aShi et al, , 2019bShi et al, , 2019c.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 3 more Smart Citations